2020
DOI: 10.1186/s13567-020-00815-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of attenuated live vaccine candidates against swine brucellosis in a non-zoonotic B. suis biovar 2 background

Abstract: Brucella is a genus of gram-negative bacteria that cause brucellosis. B. abortus and B. melitensis infect domestic ruminants while B. suis (biovars 1-3) infect swine, and all these bacteria but B. suis biovar 2 are zoonotic. Live attenuated B. abortus S19 and B. melitensis Rev1 are effective vaccines in domestic ruminants, though both can infect humans. However, there is no swine brucellosis vaccine. Here, we investigated the potential use as vaccines of B. suis biovar 2 rough (R) lipopolysaccharide (LPS) muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…We used the mouse model ( Grilló et al, 2012 ; Aragón-Aranda et al, 2020 ) to examine the contribution of PC to B. suis bv2 virulence. We observed that impairment of PC synthesis in Bs2WT by deletion of both pcs and pmtA resulted in a low degree of attenuation that only became significant at late stages of the infection ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the mouse model ( Grilló et al, 2012 ; Aragón-Aranda et al, 2020 ) to examine the contribution of PC to B. suis bv2 virulence. We observed that impairment of PC synthesis in Bs2WT by deletion of both pcs and pmtA resulted in a low degree of attenuation that only became significant at late stages of the infection ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the bacterial strains and plasmids are shown in Supplementary Table 1 . The virulent B. suis biovar 2 (bv2) strain CITA 198 (henceforth Bs2WT) was selected for this study because the reference bv2 strain B. suis Thomsen is attenuated in mice ( Aragón-Aranda et al, 2020 ). The choline-containing media used were tryptic soy broth (TSB, Scharlau, Barcelona, Spain), the same medium with 15% agar (TSA) or Blood Agar Base (BAB; Oxoid, United Kingdom), supplemented when necessary with 50 μg/ml kanamycin (Km), or/and 5% sucrose or/and 0.2% activated charcoal (Sigma) (see below).…”
Section: Methodsmentioning
confidence: 99%
“…variations depending on strain, in which "A-dominant" strains exhibit a linear α-1,2-linked polymer with approximately 2% α-1,3 linkages while the O-PS from "M-dominant" strains is a linear polymer of tetrasaccharide repeating units containing one α-1,3 linkage and three α-1,2-linked monosaccharide residues (Meikle et al, 1989;Kubler-Kielb and Vinogradov, 2013;Mancilla, 2015). Although not sufficient for speciation, serotyping using monoclonal antibodies directed against A or M epitopes can allow for distinction of different biovars within a particular smooth Brucella species (Alton et al, 1988). Further discussion of O-PS in this review will focus on the classical smooth Brucella spp.…”
Section: Lipopolysaccharide Structurementioning
confidence: 99%
“…RB51's reduced efficacy against B. ovis and its smooth counterparts in the natural host may be associated with its attenuation and/or alterations to its outer membrane or LPS outside of its lack of O-PS. Several studies have demonstrated that targeted mutagenesis can produce rough vaccines that are superior in protection to RB51 and comparable to protection by S19 or Rev.1 in mice (Monreal et al, 2003Kahl-McDonagh andAragón-Aranda et al, 2020). One prominent finding is that for a rough vaccine to be effective, the core must be intact although lack of the aforementioned lateral side branch may actually enhance vaccine efficacy, presumably due to enhanced recognition of surface molecules in the absence of this "shield" (Monreal et al, 2003;Soler-Lloréns et al, 2014).…”
Section: Vaccine Development For Rough Brucella Sppmentioning
confidence: 99%
See 1 more Smart Citation